In Vitro Effect of Dovitinib (TKI258), a Multi-Target Angiokinase Inhibitor on Aggressive Meningioma Cells. (2nd July 2020) - Das, Arabinda; Martinez Santos, Jaime L.; Alshareef, Mohammed; Porto, Guilherme Bastos Ferreira; Infinger, Libby Kosnik; Vandergrift, William A.; Lindhorst, Scott M.; Varma, Abhay K.; Patel, Sunil J.; Cachia, David
Abstract: Background: Meningiomas represent ∼30% of primary central nervous system (CNS) tumors. Although advances in surgery and radiotherapy have significantly improved survival, there remains an important subset of patients whose tumors have more aggressive behavior and are refractory to conventional therapy. Recent advances in molecular genetics and epigenetics suggest that this aggressive behavior may be due to the deletion of the DNA repair and tumor suppressor gene, CHEK2, neurofibromatosis Type 2 (NF2) mutation on chromosome 22q12, and genetic abnormalities in multiple RTKs including FGFRs. Management of higher-grade meningiomas, such as anaplastic meningiomas (AM: WHO grade III), is truly challenging and there isn't an established chemotherapy option. We investigate the effect of active multi tyrosine receptor kinase inhibitor Dovitinib at stopping AM cell growth in in vitro with either frequent codeletion or mutated CHEK2 and NF2 gene. Methods: Treatment effects were assessed using MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay, western blot analysis, caspases assay, and DNA fragmentation assay. Results: Treatment of CH157MN and IOMM-Lee cells with Dovitinib suppressed multiple angiokinases—mainly FGFRs, leading to suppression of downstream signaling by RAS–RAF–MAPK molecules and PI3K–AKT molecules which are involved in cell proliferation, cell survival, and tumor invasion. Furthermore, Dovitinib induced apoptosis via downregulation of survival proteins (Bcl-XL), and over-expression of apoptotic factors (Bax and caspase-3) regardless of CHEK2 and NF2 mutation status. Conclusions : This study establishes the groundwork for the development of Dovitinib as a therapeutic agent for high-grade AM with either frequent codeletion or mutated CHEK2 and NF2, an avenue with high translational potential.